Evaluation of Electrolyte Imbalance in Diabetic Patients Using Chemical Analysis - Samer Mohammed Ali Fadhil,; Nour Zaeem Abdullah,; Narjis Muhammad Kamil Ubaid,; Zaid Salih Bader,; Asraa Salim Abd_Ulsadda, (American Journal of Biomedicine and Pharmacy, 2025)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetes mellitus is a chronic metabolic disorder that affects millions of people globally and is anticipated to become one of the most prevalent diseases over the next 25 years. Diabetes is mainly classified into two groups which are type I diabetes or Insulin dependent diabetes mellitus (IDDM) which is an autoimmune destruction of the insulin-producing pancreatic β-cell. The other one is type II diabetes or Non-insulin dependent diabetes mellitus (NIDDM) which is a complex disorder resulting primarily from insulin resistance along with an underlying secretory defect in the β-cell. Type II diabetes is more common (90–95%) than Type I diabetes (5–10%).